ID 137 – Spinal cord tolerance to antero-posterior and lateral compression: Experimental study. Issue 3 (March 2016) - Cabañes, L.; de Blas, G.; Moreno, M Mar; Correa, C.; L.M.,; Barrios, C.; Burgos, J.
Abstract : Summary: The aim of this study is to establish, by means of neurophysiologic monitoring, the tolerance of the spinal cord to compression. Material and methods: Spinal cord was exposed through a large laminectomy in 13 domestic pigs. Progressive compression of the spinal cord was performed with a precise compression device with a pair of parallel blades that were set up antero-posteriorly or to both sides of the spinal cord, and then sequentially approximated to cause a progressive cord compression. Spinal cord to spinal cord evoked potential (EP), D-wave recordings and somatosensory epidural evoked potential (SSEP) were obtained for each approach of the sticks. Results: For progressive compression, changes on the evoked potentials were observed after a mean displacement of the sticks of 1.5 ± 1 mm for the motor EP, 1.5 ± 0.7 mm for the cord to cord EP, and 2.5 ± 1.3 for the SSEP when provoking an antero-posterior compression; and 2.9 ± 1.1 mm, 2.7 ± 1 mm, and 4.1 ± 1.3 respectively when performing the lateral compression. Conclusion: The spinal cord is more sensitive to antero-posterior compression that to lateral compression. In both cases, cord to cord EP and D-wave are the first neurophysiologic parameters to detect the injury, whereas the SSEPs are less sensitive to compression.